Three‐dimensional separate descendant‐based SPIHT algorithm for fast compression of high‐resolution medical image sequences. Issue 1 (1st January 2017) - Song, Xiaoying; Huang, Qijun; Chang, Sheng; He, Jin; Wang, Hao
Abstract : To provide a fast compression algorithm for high‐resolution medical image sequences, an efficient three‐dimensional (3D) separate descendant‐based (SBD) set partitioning in hierarchical trees (SPIHT) algorithm (3D SDB‐SPIHT) is proposed in this study. To accelerate the transformation, 3D integer wavelet transform is used first. Based on an efficient spatial–temporal tree structure, which is designed for the transformed coefficients, the authors propose a fast coding scheme by separating the descendant set into offspring set and leaves set. The proposed algorithm has more selectivity in deciding the scanning and coding of the descendant sets and hence the coding time is accelerated. Experimental results demonstrate that 3D SDB‐SPIHT compresses medical images faster compared with traditional 3D SPIHT and other variations of 3D SPIHT.